2017
DOI: 10.1002/mame.201700082
|View full text |Cite
|
Sign up to set email alerts
|

Ultralight and Flexible MWNTs/Polyimide Hybrid Aerogels for Elastic Conductors

Abstract: Aerogels have showed tremendous potential applications because of its unique and outstanding properties. Herein, a novel two‐step approach to form self‐assembly nanocomposite aerogels driven by the strong interactions between water‐soluble polyimide (PI) precursor polyamic acid salt (PAAs) and hydroxyl multiwalled carbon nanotubes (MWNTs‐OH) is reported. The PI therein constitutes the framework of the nanocomposite and raises the strength of the cell walls, which endows aerogels with superelasticity and robust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…indicating more superior elasticity and fatigue resistance compared with compressible carbon aerogels or sponges, 39,40 and porous composite aerogels or foams. [41][42][43][44][45] Besides, the stress-strain curves of the PI/rGO-5, PI/rGO-10, PI/rGO-15 aerogels at different strain rates (5-150 mm min À1 ) almost overlap, indicating that the composite aerogels can maintain excellent compression stability even under rapid deformation ( Fig. 3f and S7 †).…”
Section: Resultsmentioning
confidence: 91%
“…indicating more superior elasticity and fatigue resistance compared with compressible carbon aerogels or sponges, 39,40 and porous composite aerogels or foams. [41][42][43][44][45] Besides, the stress-strain curves of the PI/rGO-5, PI/rGO-10, PI/rGO-15 aerogels at different strain rates (5-150 mm min À1 ) almost overlap, indicating that the composite aerogels can maintain excellent compression stability even under rapid deformation ( Fig. 3f and S7 †).…”
Section: Resultsmentioning
confidence: 91%
“…Loss also increases by the incorporation of the Sn‐polyesters, mostly in the higher frequency regions. Lower loss is observed for the pDMTDMG hybrids (0.007–0.041) compared to pDMTGlu hybrids (0.009–0.058), which is much lower than any known hybrid system . Their trends in the κ and tan δ at 1 kHz in room temperature are shown in Figure C,D for all compositions.…”
Section: Experimental Dielectric Constant (κ) and Dissipation Factor mentioning
confidence: 81%
“…Recently, polyimides (PIs) containing hybrid materials are of great interest and are receiving extensive consideration due to their improved morphological, thermal, and electrical properties . PI with a dianhydride, 3,3´,4,4´‐benzophenonetetracarboxylic dianhydride (BTDA), and an aliphatic diamine linker 1,6‐hexadiamine (HDA) was also synthesized by our team .…”
Section: Experimental Dielectric Constant (κ) and Dissipation Factor mentioning
confidence: 99%
“…This indicated that the PI aerogel prepared by ice crystal‐induced self‐assembly still had excellent thermal stability. Due to the hydrolysis of PAA during the preparation of PAA powder from the purchased PAA solution, the molecular weight of PI would also decline. As a result, the initial decomposition temperature of PI aerogel prepared with 8 wt % PAA was 8 °C lower than that of PI film and 8 °C higher than that of PI aerogel prepared with 6 wt % PAA due to the lower water content and less hydrolysis of PAA.…”
Section: Resuls and Discussionmentioning
confidence: 99%